2003
DOI: 10.1016/s1063-4584(03)00170-5
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the collagenase-3 endocytotic receptor system in cells from patients with osteoarthritis

Abstract: These results suggest a mechanism whereby impaired receptor-mediated removal of collagenase-3 in OA chondrocytes may lead to enhanced local degradation of the cartilage matrix. This work also implicates an LRP family member in endocytotic receptor-mediated collagenase-3 processing and suggests a novel therapeutic target for OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…Lowering the concentration of ADAMTS-4 clearly demonstrated that 3-5-fold less GAG is released from live cartilage compared with dead cartilage. Subtraction of the basal levels of GAG release from live and dead cartilage also unmasked the significantly reduced GAG release in live cartilage incubated with MMP-13 (data not shown), which has previously shown to be endocytosed by chondrocytes via LRP1 (28,29). LRP1-mediated endocytosis is, therefore, a newly discovered mechanism for regulating ADAMTS-4 activity in cartilage.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Lowering the concentration of ADAMTS-4 clearly demonstrated that 3-5-fold less GAG is released from live cartilage compared with dead cartilage. Subtraction of the basal levels of GAG release from live and dead cartilage also unmasked the significantly reduced GAG release in live cartilage incubated with MMP-13 (data not shown), which has previously shown to be endocytosed by chondrocytes via LRP1 (28,29). LRP1-mediated endocytosis is, therefore, a newly discovered mechanism for regulating ADAMTS-4 activity in cartilage.…”
Section: Discussionmentioning
confidence: 69%
“…This led us to discover that ADAMTS-5 is endocytosed via LRP1 by viable chondrocytes. In those studies we observed no significant differences in aggrecan degradation between live and dead cartilage when ADAMTS-4, MMP-1, or MMP-13 was added (17), although MMP-13 has been reported to be endocytosed by chondrocytes via LRP1 (28,29). However, the concentrations of ADAMTS-4 and MMP-13 used in those studies were 10-fold higher than that of ADAMTS-5, as ADAMTS-5 is the most active aggrecanase (10,11).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Internalization of MMP-13 is mediated by a 170-kDa receptor both in rodent cells and in human chondrocytes (Walling et al, 2003). As mentioned above, MMP-13 is expressed in RA, an arthritic disease characterized by chronic inflammation and cartilage destruction.…”
Section: Neoplastic Diseasesmentioning
confidence: 94%
“…In studies of patients with juvenile idiopathic arthritis, MMP-13 was also undetectable in serum and synovial fluid (26), while other authors have detected MMP-13 in the serum of patients with osteoarthritis (27,28). It has been suggested that levels of MMP-13 in RA patients may be low due to active removal and degradation by chondrocytes and synoviocytes via a specific surface MMP-13 receptor (29)(30)(31).…”
Section: Young-min Et Almentioning
confidence: 99%